GUIDANCE LEARNED FROM HOME EDUCATIONAL SOLUTIONS DURING COVID 19 PANDEMIC IN KEDUNGBOKOR BREBES VILLAGE - Pramesta, Anggit; Basyar, Jofinda Tandan; Niswatun Fauziyah, Niswatun; Lestari, Putri Dwi; Junaeri, Tiara Wulan; Riansyah, Wahyu Rizki (Universitas Negeri Semarang, 2020)
Home learning guidance is necessary during the covid-19 pandemic, where all the usual face-to-face learning activities in schools are no longer carried out. The Ministry of Education publishes regulations so that all learning activities in the school are carried out in each student's home. In studying at home students need guidance from parents or guardians to accompany them. Through the study guidance conducted by kkn BMC UNNES 2020 students as a form of community service can help students who are difficult in the learning process at home during this covid-19 pandemic. The methods used in the implementation of this study guidance are the method of lectures, and q&A between the student and the student. Bimbingan belajar dari rumah sangat diperlukan di masa pandemi covid-19 ini, dimana semua kegiatan pembelajaran yang biasa dilakukan secara tatap muka di sekolah tidak lagi dilaksanakan. Kemendikbud menerbitkan peraturan agar semua kegiatan pembelajaran di sekolah dilakukan di rumah masing-masing siswa. Dalam belajar dirumah siswa membutuhkan adanya bimbingan dari orang tua atau pun walinya untuk mendampinginya. Melalui bimbingan belajar yang dilakukan oleh mahasiswa KKN BMC UNNES 2020 ini sebagai bentuk pengabdian masyarakat dapat membantu siswa yang kesulitan dalam proses belajar di rumah pada masa pandemi covid-19 ini. Metode yang digunakan dalam pelaksanaan bimbingan belajar ini yaitu metode ceramah, dan tanya jawab antara mahasiswa pembimbing belajar dan siswa.